P286 Implementing a COPD Discharge Care Bundle: The Challenges and Facilitators Revealed. (19th November 2012) - Musgrave, H; Howe, C; Green, S; Lennox, L; Elkin, S; Wilson, S; Mann, B; Lai, D
Abstract : Introductions/Objectives: The National Institute for Health Research (NIHR) Collaboration for Applied Health Research and Care (CLAHRC) for Northwest London worked with clinicians and patients to develop a COPD discharge care bundle, which has been implemented across 7 acute hospitals using quality improvement (QI) methodology. The aim of this study is to identify the challenges encountered by teams in implementing the care bundle and the associated solutions and facilitators which will inform future implementation across other sites. Methods: An initial retrospective documentary analysis of data from the clinical implementation teams was undertaken. Data sources included minutes from 6, 12 and 18 month review meetings as well as contemporaneous records documented by the implementation team. The second stage involved collaborative learning workshops with 4 implementation teams. These workshops focused on reviewing the challenges identified in the first stage of analysis and identifying any challenges that had been missed. A discussion followed where the teams identified the solutions and facilitators that were developed during the project. Results: The first stage of analysis identified a number of challenges, some of which were common to all sites. The most common challenges related to the 5 following high-level themes: staffing, infrastructure, process, QI methodology and patient and public involvement. Within these themes 28 key challenges were identified. In the second stage of analysis teams demonstrated that they had developed solutions to address specific challenges. For example, a project team shared their experience of a mapping session which helped them better understand the flow of patients in their setting and led to improvements in compliance to the COPD discharge care bundle. Conclusions: There has been increasing enthusiasm to adopt the COPD bundle across the region but the implementation of new interventions poses challenges to both those planning and delivering such initiatives. Understanding and learning from the challenges faced by previous endeavours and the facilitators to overcoming these barriers provides an opportunity to mitigate issues that cost time and resource and ensure training tailored to the anticipated challenges.